2021
DOI: 10.1136/bmjgh-2020-004213
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial influences on help-seeking behaviour for cancer in low-income and lower middle-income countries: a mixed-methods systematic review

Abstract: IntroductionStarting cancer treatment early can improve outcomes. Psychosocial factors influencing patients’ medical help-seeking decisions may be particularly important in low and lower middle-income countries (LMIC) where cancer outcomes are poor. Comprehensive review evidence is needed to understand the psychosocial influences on medical help-seeking for cancer symptoms, attendance for diagnosis and starting cancer treatment.MethodsMixed-methods systematic review registered on PROSPERO (CRD42018099057). Pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 92 publications
1
43
0
Order By: Relevance
“…Our previous research with high-risk individuals in Ireland found that stories of misdiagnosis caused mistrust in the healthcare system among some participants, which led them to delay help-seeking for symptoms of LC [ 13 ]. Additionally, a recent systematic review of 64 studies on psychosocial factors influencing cancer help-seeking found that mistrust in medicine deterred patients from seeking medical help for cancer, particularly in low-income and lower middle-income countries [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research with high-risk individuals in Ireland found that stories of misdiagnosis caused mistrust in the healthcare system among some participants, which led them to delay help-seeking for symptoms of LC [ 13 ]. Additionally, a recent systematic review of 64 studies on psychosocial factors influencing cancer help-seeking found that mistrust in medicine deterred patients from seeking medical help for cancer, particularly in low-income and lower middle-income countries [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we observed that women with no delay and great delay similarly reported the use of alternative treatment prior to seeking medical attention. The preference for alternative treatment is commonly reported in this region (14,20,22) as well as other LMICs (8), and has been previously shown to deter help-seeking behaviour (23). Here, we suggest that use of alternative treatment may not always lead to delays in help-seeking.…”
Section: Discussionmentioning
confidence: 95%
“…This finding is comparable to past studies of Asian women, where poor social support and negative social influences are often reported as primary barriers to seeking help for breast cancer symptoms (15,20,21), and may be a more significant barrier than lack of knowledge in this region (22). In Asian communities, family members appear to have both direct and indirect roles in a women’s decision to seek help (14,23,24). A supportive family can be an enabler of early help-seeking behavior and adherence to treatment (14), whereas lack of support or unstable family dynamics often lead to confusion, uncertainty, and ultimately, delay in seeking medical treatment (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McCutchan et al conducted a systematic review of psychosocial influences on help-seeking behavior in LMICs (96). They found that the use of traditional, complementary and alternative medicine was a key barrier to medical help-seeking in LMICs, and was influenced by causal beliefs, cultural norms, and a preference to avoid biomedical treatment.…”
Section: Individual Levelmentioning
confidence: 99%